A Analytical Study on Global Bank Non Performing Assets Management with Reference to India (International Journal of Food and Nutritional Sciences, 2022)
The global NPA problem has been a concern, particularly during economic downturns or financial crises. Worldwide NPA issue can vary from nation to nation. It is based on economic conditions, regulatory frameworks, and lending practices. Effective management and resolution of NPAs often require coordinated efforts among governments, central banks, and financial institutions to prevent systemic risks and support economic recovery. It's essential to consider the specific context of each country while figuring out the global NPA problem. Non-Performing Assets or NPAs is one of the important challenges in financial market of Indian economy. The Non-Performing Assets (NPAs) issue of Indian economy especially in banking sector has become the subject of much concern. Escalating NPA figures can bring economic recessions or downturns, as individuals and businesses struggle to meet their loan obligations. Weaknesses in banking regulations, inadequate risk assessment, and poor government control over lending standards can contribute to the accumulation of NPAs and NPAs can be concentrated in specific sectors such as real estate, infrastructure, or agriculture, depending on the economic conditions and lending practices in a particular region. Indian NPA problem is a complex issue, and addressing it requires a multi-faceted approach involving reforms in the banking sector. The present research paper is planned to explore NPA complication in world as well as in Indian economy.